Perlindungan Hukum bagi Atlet dalam Perjanjian Kontrak Kerja Berkaitan dengan Hak Kerja dalam Pasal 27 Ayat 2 UUD 1945 - Ashari Efendi; Seri Mughni Sulubara (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The purpose of this research is to find out the legal protection for athletes in labor contract agreements related to employment rights in Article 27 Paragraph 2 of the 1945 Constitution. Article 27 Paragraph 2 of the 1945 Constitution reads "Every citizen has the right to a job and a livelihood that is worthy of humanity". The research method used is descriptive qualitative research with a normative juridical approach. Qualitative descriptive research with a normative juridical approach is research that tries to describe an event or event that occurs directly, real, realistic, actual in existing rules. Protection of athletes through positive law in the form of legislation is a legal norm that must be obeyed in the life of the state. Basically, the protection of athletes is intended to ensure equal opportunity and treatment without discrimination on any basis to realize the welfare of athletes in Indonesia.